Leadership development as a dialogic process: the rationale and concept of an international leadership institute. Issue 2 (14th March 2016) - Kedian, Jeremy; Giles, David; Morrison, Michele; Fletcher, Murray
Abstract : Rapidly changing educational contexts demand deft leadership responses. In this fluid environment, it is imperative that leadership learning models sound educational praxis. Such praxis necessitates the inclusion of participant voices within relational and dialogic processes that enable authentic, creative and collaborative thinking. This paper studies the fourth International Leadership Institute, a four-day extended dialogue which saw 70 educational leaders from six countries meet in New Zealand to consider the theme of educational futures. We outline the rationale, practices and outcomes of this alternative approach to leadership learning, an approach which holistically engages participants within and across educational sectors. Participants and facilitators alike attest to the transformative influence that this relational encounter has on their 'being' as leaders, and provide compelling reasons why contemporary leadership learning approaches should privilege genuine dialogue.